2014 IEEE International Solid-State Circuits Conference Digest of Technical Papers (ISSCC) 2014
DOI: 10.1109/isscc.2014.6757485
|View full text |Cite
|
Sign up to set email alerts
|

23.2 A 1.1nW energy harvesting system with 544pW quiescent power for next-generation implants

Abstract: This paper presents a nW power management unit (PMU) for an autonomous wireless sensor that sustains itself by harvesting energy from the endocochlear potential (EP), the 70-100 mV electrochemical bio-potential inside the mammalian ear. Due to the anatomical constraints inside the inner ear, the total extractable power from the EP is limited to 1.1-6.25 nW. A nW boost converter is used to increase the input voltage (30-55 mV) to a higher voltage (0.8 to 1.1 V) usable by CMOS circuits in the sensor. A pW Charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Here, P TX,leak is the transmitter leakage power, E b is the energy required to transmit a single bit, N is the number of bits per packet (programmable from 8–128 bits based on a binary counter), and T pkt,int is the time interval between packets (programmable from 40–360 s based on a counter that is driven by the 12.8 Hz on-chip oscillator found in the boost converter control circuitry [10]). Based on this equation, the transmitter must not only have extremely low leakage power, it also must be very energy efficient during active-mode in order to achieve the necessary overall power goal, otherwise the effective bit rate (i.e.…”
Section: Transmitter Architecturementioning
confidence: 99%
See 3 more Smart Citations
“…Here, P TX,leak is the transmitter leakage power, E b is the energy required to transmit a single bit, N is the number of bits per packet (programmable from 8–128 bits based on a binary counter), and T pkt,int is the time interval between packets (programmable from 40–360 s based on a counter that is driven by the 12.8 Hz on-chip oscillator found in the boost converter control circuitry [10]). Based on this equation, the transmitter must not only have extremely low leakage power, it also must be very energy efficient during active-mode in order to achieve the necessary overall power goal, otherwise the effective bit rate (i.e.…”
Section: Transmitter Architecturementioning
confidence: 99%
“…The transmitter receives its supply voltage, V DD , from an on-chip boost converter whose details are discussed in [10]. The value of V DD is set by a balance between the amount of energy extracted from the EP and the power of the load circuits.…”
Section: Circuit Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%